2008
DOI: 10.1177/039463200802100421
|View full text |Cite
|
Sign up to set email alerts
|

Early Cytokine Modulation after the Rapid Induction Phase of Sublingual Immunotherapy with Mite Monomeric Allergoids

Abstract: The influence of different treatment schedules of sublingual immunotherapy (SLIT) in activating IL-10-producing T-cells, crucial in inducing allergen-specific tolerance, is not completely understood. The present work was designed to evaluate allergen driven interleukin release by mononuclear cells in the early phase of SLIT, after application of different induction schemes. Twenty mite-allergic patients were enrolled, 10 (group A) treated with a traditional 98 day induction scheme and 10 (group B) with a 16 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…However, in our trial, the modulation of IL-l°did not occur; this finding could be due to the timing chosen for cytokine determination. In fact, the increase in IL-I0 has been observed in short-term studies of 2-6 months (13,18,20,21), whereas our laboratory assessments were carried out after one year of treatment. The timing in detecting such immunological change is of crucial importance.…”
Section: Discussionmentioning
confidence: 94%
“…However, in our trial, the modulation of IL-l°did not occur; this finding could be due to the timing chosen for cytokine determination. In fact, the increase in IL-I0 has been observed in short-term studies of 2-6 months (13,18,20,21), whereas our laboratory assessments were carried out after one year of treatment. The timing in detecting such immunological change is of crucial importance.…”
Section: Discussionmentioning
confidence: 94%
“…Also, recent scientific interest has been focused on eliciting regulatory T cells (Treg) capable of downregulating both Th1 and Th2 responses through the production of interleukin (IL)-10 and/or transforming growth factor (TGF)-β [14,15,16,17]. Furthermore, preliminary clinical studies on SLIT indicated a similar early Treg-related interleukin production with consequent downmodulation of the immune response [18,19,20]. Although there have been several important studies published, most have been associated with particularly long periods of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be related to the favorable cytokine changes (allergen-specific activation of IL-10 secreting Treg lymphocytes) shown in previous studies with the same immunotherapy (mite allergoid SLIT) (15).…”
Section: Discussionmentioning
confidence: 54%
“…A timeresponse effect was observed by Di Gioacchino et al in an immunological study comparing the effects on IL-IO and other cytokines (INF-y, IL-4, IL-6, IL-2, TNF-a) of two different SLIT induction schemes, one lasting 14 weeks and the other 16 days. The faster administration, with patients taking the tablets at shorter intervals, was associated with greater changes in these parameters, regardless of the total amount of allergen administered (15).…”
Section: Discussionmentioning
confidence: 91%